Few layer 2D pnictogens catalyze the alkylation of soft nucleophiles with esters - Vicent Lloret (Nature Portfolio, 2019)
Group 15 elements in zero oxidation state, also called pnictogens, are rarely used in catalysis due to the difficulties in preparation. Here, the authors report on the synthesis of highly exfoliated, few layer 2D phosphorene and antimonene in zero oxidation state, and their use as efficient catalysts for the alkylation of nucleophiles with esters.